Introduction: Colonial Public Spheres and the Worlds of Print. Issue 2 (August 2020) - Hunter, Emma; James, Leslie
Abstract: A growing literature explores the varying role of print media in the colonial world and the new types of publics such newspapers and periodicals produced. However, this literature has tended to focus on specific regions, and has often sidestepped the larger question of how to conceptualise the relationship between print media and colonial rule. While some have used the term 'colonial public sphere' or 'colonial publics, ' others have preferred to avoid these terms and instead thought in terms of multiple and overlapping publics. What this literature has shown is that a single analytic model for analysing public spaces of discourse is not usable. In this Introduction to our Special Issue we propose a new framework for studying the publics created through print media in the colonial world. We outline a set of four factors – addressivity, performativity, materiality and periodicity – that can be applied to specific historical case studies. We then explain how the issue as a whole models this methodology as a means to analyse how print media (as one medium within the public sphere) functioned in specific colonial and semi-colonial spaces around the world.